ANTI FUNGAL ACTIVITY OF WOOD EXTRACT OF Aquilaria crassna Pierre ex Lecomte AGAINST AGARWOOD-INDUCING FUNGI, Fusarium solani - Eka Novriyanti; Erdy Santosa; Wasrin Syafii; Maman Turjaman; Irnayuli R. Sitepu (Indonesian Journal of Forestry Research, 2010)
This paper provided information regarding artificial agar wood production. Fungi are considered as biological agent for agarwood formation and agarwood is assumed as tree defense mechanism product. This research was aimed at investigating the anti fungal activity (AFA) of Aquilaria crassna, one of the agar wood-producing trees, against Fusarium solani in vitro. Aquilaria crassna wood mill was extracted by 70% ethanol to investigate the anti fungal activity. The result are Aquilariacrassnaexhibited low extractives content, which was only 2.0% (w/w) and a low anti fungal activity in vitro, especially for ethanol extract. However, further fractionation and bioassay showed that the most active component was likely in the ethyl-acetate soluble fraction that exhibited strong anti fungal activity (52.5%) at 4.0% of concentration.